THE EFFECT OF DEVELOPMENT AND TREATMENT GROUP COUNSELLING ON THE RESILIENCY OF DELINQUENT STUDENTS - Khalid, Nurul Fazzuan; Jais, Samsiah Mohd; Zainal3, Muhammad Zuhair (International Journal of Psychosocial Rehabilitation, 2020)
This experimental study was conducted based on two main objectives. First, to measure the effect of Development and Treatment Group Counselling (KKPR) on resiliency between treatment groups and control groups. Second, to measure the impact of Development and Treatment Group Counselling (KKPR) on resiliency between marathon treatment groups, weekly treatment groups and control groups. A total of 60 subjects were divided into three groups consists of weekly treatment group, marathon treatment group and control group. Pre-test and post-test data were collected through The Resiliency Scale and analysed descriptively and inferentially through statistical test of mean, MANCOVA and Post-Hoc Tukey at the significance level of 0.05. The results showed that first, was significantly effective in increasing resiliency of subjects in treatment group compared to the subjects in control group. Second, KKPR more effective on the weekly treatment group compared to the marathon treatment group. As a conclusion, KKPR is effective to improve resiliency among the subjects in treatment group. Overall, the outcomes of this study give a new perspective theoretically and practically in the field of counselling and psychology in order to address the delinquent behavior among students.